IDENTIFIKASI PREDATOR DAN PARASITOID PADA TANAMAN CABAI (Capsicum annum) - Garusu, Muh. Indra; Anshary, Alam; Wahid, Abdul (AGROTEKBIS, 2019)
This study aimed to determine the function of predators and parasitoids found in the of research site of chili cultivation in Sidera Village, Biromaru Sub-District, Sigi District. The predator and the parasitoid identification were done at the Laboratory of Plant Pest and Disease Tadulako University. This research was conducted in May-July 2016. A preliminary survey was conducted in the field in order to determine the area of samples for observation points followed by collecting the insect samples as material for analysis in the laboratory. The samples were caught using traps and sweep net, and the samples were then kept in a jar containing alcohol. There are nine species of predatory insects i.e. Mantis religeosa, Harmonia Axyridis, Coccinella septempunctata, Cycloneda munda, Liriothermis, Orthermis ferruginea, Libellula, Oxyopes sertatus and and Selonopsis sp. and one species parasitoid Aphidius aquilus.